Transport and energy proceedings of a conference held in London on 17-18 November 1980 and organized by the Institution of Civil Engineers in association with the Chartered Institute of Transport ... [et al.]. (Telford for the Institution, 1981)
These papers highlight future demand for transport by road, rail and air, and focus on ways to reduce their dependence on oil with different technologies. Prospects for the future are discussed.